Território e direiro territorial: resistência para além do direito à moradia dos acabamundenses. - Daniel Pinheiro Viegas (2020)
This thesis presented refers to a context of territorial dispute that is extremely conducive to exposing the problem of the use of law as a legitimizing instrument of violence that is consortiated by the market with the state, based on reflections on the Community of Vila Acaba Mundo, in Belo Horizonte, Minas Gerais, to answer the problem of the limits of legal categorizations, and to demonstrate the insufficiency of the positive law in the face of a territory, which is a spatial construction of the social relations of power within the struggles for recognition, redistribution and representation, in dynamic processes resistance, with material and / or intangible boundaries. From this perspective, it is a continuation of the critical reflections of Salcedo Repolês (2010) to the theoretical insufficiency of the concept of nation-state for the formation of a single identity plus a concept of an equally open territory, which the end-worlds allow to understand it as inadequate. comprehensive category, as well as a totalizing identity such as that of the favelado, as there is an identity component present in social relations, which is no longer referred to an economic category. In this sense, through empirical research, with ethnographic instruments, I demonstrate the social unity composed of the social agents referred to Vila Acaba Mundo and their identity of situational convergence. I describe the processes of territorialization of the Community in which cultural and religious practices led to a genealogical relationship with Chico Rei, in which ancient traditions operate new connections and meanings, up to the political- organizational performance through the ties of solidarity between the women of the world, whose sorority transmutes the social unit into a mobilization unit, aimed at the construction of a specific territoriality. These data allow, in a political dimension of three-dimensional justice, to reflect that representation is central to the process of end-world resistance, antagonistic to the very grammar of the legal framework, and which presents the elaboration of a transformative agenda, in which the principle of the territorial State does not more guarantees an adequate basis to determine the “who” is in the dispute of justice, but to question “how”, regarding the accepted procedures to determine the subjects of law.